Development of Case-Based Electronic Student Worksheets (E-LKPD) on Carbohydrate Metabolism Disorders for Science Education Students - Qomaliyah, Eka Nurul; Habiddin, Habiddin (Chemistry Education Practice, 2025)
Biochemistry is one of the courses that encompasses broad and complex material, including metabolism. Students’ understanding of carbohydrate metabolism is often limited to theoretical and memorization aspects. Therefore, it is necessary to develop learning media that support interactive and more meaningful learning. This study aims to develop a case-based Electronic Student Worksheet (E-LKPD) on carbohydrate metabolism disorders for students in the Science Education Program. The research employed the Research and Development (R&D) method with the development stages of Define, Design, and Develop. Data were obtained from expert validation as well as user response questionnaires involving 25 science education students. The results of material validation, language validation, and output validation showed “high validity and feasibility,” while user questionnaires indicated an average 90% “very good” response and agreement to use the E-LKPD in Biochemistry learning. Thus, the case-based E-LKPD on carbohydrate metabolism disorders is considered feasible to be used as a learning medium in Biochemistry courses, particularly in supporting case-based and student-centered learning.